Characterization and Properties of Ultra-High Molecular Weight Polyethylene 1998
DOI: 10.1520/stp11909s
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-Transform Infrared (FTIR) Oxidation Analysis of Ultra-High Molecular Weight Polyethylene (UHMWPE) Implants: Possible Contamination from Synovial Fluid and Serum

Abstract: Oxygen-containing chemical species may cause an artificially high level of measured oxidation in the infrared (IR) analysis of clinically retrieved or hip wear simulator tested ultra-high molecular weight polyethylene (UHMWPE) implants. Esterified fatty acids from the synovial fluid or calf serum commonly used in the hip or knee wear simulators are the most likely source of contamination. No such interference is encountered in the IR analysis of shelf-aged UHMWPE components that have never been implanted. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Thin sections (200 μm) created using a microtome were also prepared in worn and unworn locations and boiled in heptane for 6 hours to remove absorbed lipids [22]. The oxidation index through the thickness of the liners was then analyzed following ASTM 2102.…”
Section: Methodsmentioning
confidence: 99%
“…Thin sections (200 μm) created using a microtome were also prepared in worn and unworn locations and boiled in heptane for 6 hours to remove absorbed lipids [22]. The oxidation index through the thickness of the liners was then analyzed following ASTM 2102.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to hexane extraction, the carbonyl absorption spectrum near the surface in the worn areas of the clinically retrieved cups and the wear tested cups had a peak at 1740 cm Ϫ1 , corresponding to contaminants of proteins or esters. 8,34 After extraction the peak near the surface (i.e., between about 0.5 and 1 mm deep) shifted to 1736 cm Ϫ1 , corresponding to aldehyde groups (OCHO). At sites deeper than this the peak occurred at 1717 cm Ϫ1 , corresponding to a ketone ͩ { } CAOͪ.…”
Section: Effect Of Hexane Extraction On Apparent Level Of Oxidationmentioning
confidence: 99%
“…Li and colleagues suggested that the material containing esters was chemically bound to the bulk of the PE and was therefore not an absorbed contaminant. 36 More recently, Sun et al 34 analyzed the oxidation in "thin" microtomed sections of UHMW acetabular cups from laboratory wear tests and clinical retrievals. The absorption peak at 1740 cm Ϫ1 was essentially eliminated after ultrasonic washing in heptane, such that the apparent oxidation index decreased from 30 to 58% in the articulating region.…”
Section: Figurementioning
confidence: 99%
“…Both rim and articular surfaces were tested three times at the depths of 0.5–3.0 mm at 0.5 mm intervals. These depths were chosen based on the peak rim subsurface OI as described in prior FTIR testing by Decker and colleagues 34,36–38 …”
Section: Methodsmentioning
confidence: 99%
“…These depths were chosen based on the peak rim subsurface OI as described in prior FTIR testing by Decker and colleagues. 34,[36][37][38]…”
Section: Microindentaion Testingmentioning
confidence: 99%